Does clinical assessment really reflects what cleft patients wants? - Chi Adam, Khairul Bariah; Ismail, Siti Mazlipah; Halil, Haikal (IIUM Press, International Islamic University Malaysia, 2018)
With the increasing availability of medical and dental treatments, it would be useful to ascertain how assessment of cleft-related facial deformity could help to plan for further treatment and identify the stigmata of residual deformity.Many researches have indicated that perceived need of treatment among the parents is an important role in determining the success of healthcare delivery in cleft lip and palate patients. Therefore, this indicates the need to compare the actual treatment need with the parents’ perceived need. Therefore, the aim of this book is toinvestigate the treatment need and perceived need in cleft lip and palate individuals aged 12 years old and above. Aquestionnaire guided interview was done on 47 parents of cleft lip and palate patients to obtain demographic data, treatment history, effect of cleft on the social behaviour of the child and perceived need of treatment from few centres in Malaysia. Clinical examinations were performed on cleft lip and palate patients including evaluation of malocclusion, the need for other dental treatment and surgical management. This was followed by gross speech assessment.Finally, 3D photographs were taken for all cleft patients and deformity was evaluated by one Consultant Oral Surgeon to assess on further treatment need. As a result, we found that unilateral cleft lip and palate showed highest group in perceived need in further treatment for dental treatment, bone graft, nose and others as compared to other types of cleft. Highest perceived need for treatment was shown in descending order is perceived need for further treatment of teeth, followed by nose and alveolus in all types of cleft.We also found that there were poor to slight agreement between parents’ perceived need of treatment and professional’s assessment on treatment need (Kappa= -0.114 to 0.313).as a conclusion from this study, it can be concluded that there is a difference between perceived need and the treatment need for cleft lip and palate treatment.